Economic Impact of the European Green Deal on V4 Countries - Tsintsadze, Ana; Kotrba, Vojtěch; Dungl, Daniel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
The diploma thesis investigates the impact of the European Green Deal (EGD) initiatives on the Visegrad Group (V4) economies. The EGD was proposed in December 2019. The V4countries are emission-intensive, thus, examining the relationship between environmental protection, technological advancement, and economic growth requires further attention. The time-series data between 2000-2022 are employed for the Multiple Linear Regression model, which is an extension of the simple OLS regression. The hypothesis aims to investigate whether the EGD has a positive significant impact on the V4 economies. The variables utilised for the study include renewable energy resource production, final primary energy consumption per capita, GHG emissions, GDP per capita, research and development, and environmental protection investments. The diploma thesis references different economic theories and concepts that align with the research topic. The Environmental Kuznets Curve depicts the environmental progress as the economy experiences growth. The empirical part highlights that the environmental degradation expressed in GHG emissions is expected to decrease as energy investments increase. The research reveals the importance of strong institutions to facilitate the implementation of energy policies, which aligns with the theories of environmental economics. As the EGD is currently in its early stages, the data is inconsistent and thus, separate regressions are employed for each country. Overall, this research reveals that the EGD has mixed effects on the V4 economies. Some of them could include but are not limited to increased share of renewable resources in their energy mix. While job losses in industrial sectors are inevitable, the green jobs are slowly increasing because of EU funds’ support.
Vedoucí práce: Vojtěch Kotrba
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses